THE EFFECTIVENESS OF CO-CONTRACTION EXERCISE WITH EXTERNAL CLUE FOR QUALITY RULES IN INDIVIDUAL KNEE OA PATIENTS: SINGLE CASE REPORT - Septiani, Icha; Wahyuni, W; Perdana, Suryo Saputra (Academic Physiotherapy Conference Proceeding, 2021)
Introduction: Osteoarthritis (OA) is one of the most common conditions that cause disability, especially in the elderly population. Osteoarthritis (OA) is a degenerative and chronic disease of the knee joint. The recommended intervention is Task-Specific Training with Co-Contraction, namely muscle co-activation (coordinated agonist and antagonist muscle activity simultaneously) for joint stability, even in OA knee individuals who function dynamically as a stabilizer, controlling movement during walking. Augmented feedback (External Clue) commonly used in clinical practice and can play an important role in motor learning. Case Presentation: Mrs. S is 68 years old. The patient has a height of 155 cm and a weight of 70 kg. Mrs. S works as a housewife. The patient had this complaint several years ago. There is no history of illness in the family. Supporting data in the form of X-ray with the interpretation of knee osteoarthritis grade 2. The patient also suffered from mild deformity of the foot towards varus , the presence of crepitus, but the patient did not have local oedema , the absence of pes anserinus bursitis and the absence of joint tendenes. Management and Outcome: The patient underwent treatment consisting of Task-Specific Training based on Co-Contraction/ Co-contraction with External Clue. The patient is instructed to contract the muscles while walking. Coactivation occurs when the flexor muscles are active during the moment of extension. (External Clue) is the therapist providing additional information about the performance of motor skills so that the patient can get feedback from the patient himself. The data analysis used in this study is a single case report. The design for this study used the ABA design. The sampling technique is the consecutive method with 1 person who fits the inclusion criteria. The research measurement instrument related to the quality of walking used the 6 Minute Walking Test (6MWT). The data analysis technique used descriptive analytic. This exercise program uses Task- Specific Muscle Co-contraction Training with External Clue for one week starting from January 7 to January 14, 2020, with Ethical Clearance Letter no. 2682/B.2/KEPKFKUMS/ XI/2019 conducted by the Health Research Ethics Commission (KEPK) FK UMS. Discussion: The subjects of this study have typical symptoms of osteoarthritis of the knee, so there is no need for additional examinations to diagnose knee osteoarthritis. This is supported by the existence of pain, stiffness, and locomotor which are common symptoms of knee OA that is focused on a functional approach, namely component important in locomotor retriction is running. Task- specific training is understanding how distraction-based exercise can affect certain functional tasks which helps improve exercise protocols for people with knee OA. The concept of muscle coactivation from a specific task is muscle co-activation (coordinated agonist and antagonist muscle activity simultaneously) for joint stability, even in OA knee individuals who function dynamically as a stabilizer, controlling movement during walking. Muscle co-activation to help stabilize the joints in the ligaments and distribute pressure on the joint surfaces. Conclusion: There was a significant increase in individual walking distance of osteoarthritis knee patients.